THU0001 GENOME-WIDE ASSOCIATION STUDY ON JOINT EROSIONS IN RHEUMATOID ARTHRITIS SUPPORTS DIFFERENTIAL PATHOLOGICAL MECHANISMS ACCORDING TO ANTI-CCP STATUS. (2nd June 2020) - Julià, A.; Blanco, F.; Fernandez, B.; Gonzalez, A.; D, J.; Maymó, J.; Alperi-López, M.; Olive, A.; Corominas, H.; Martinez Taboada, V.; González-Álvaro, I.; Fernandez-Nebro, A.; et al.
Abstract : Background: Joint damage is the pathological hallmark of rheumatoid arthritis (RA). To identify the genetic variation associated with a higher level of erosions has proven elusive. Objectives: The objective of the present study was to perform a genome-wide association study on joint damage in a cohort of RA patients of the Spanish population. Our aims were to provide independent validation of previously reported variants and to identify new candidate risk loci. A stratified analysis was performed based on positivity to ACPA status. Methods: A total of 1, 135 patients diagnosed with RA using the ACR-EULAR criteria recruited by the IMID Consortium were genotyped using a 550, 000 single-nucleotide polymorphism array. Additional SNPs were imputed using the 1KG genome data. Joint damage was performed using the S-score, a simplified radiographic erosion score that has a high correlation with the Sharp-van der Hejde score (1). Association testing of SNPs with joint damage was performed via linear regression with the addition of the years of evolution as covariate. The two main components of genetic variation were also added to adjust for potential population stratification. A total of 50 SNPs representing previously reported loci associated with joint damage were selected. Genetic association was also performed at the pathway level using Pascal. Results: 45 out of 50 SNPs representing 31 previously reported loci for joint damage could be satisfactorily imputed. Association testing of the whole patient cohort replicated the association with IL2RA and TRAF1 . Of relevance, after stratifying for anti-CCP five new loci were replicated: KIF5A and SOST in ACPA-positive RA and CD40, DKK1 and TNF in ACPA-negative RA. IL2RA was only significant in the ACPA-positive group and TRAF1 was not significant in either strata. GWAS on the ACPA-positive cohort and on the ACPA-negative group identified n=7 and n=18 loci with P-values < 1x10-5, respectively. From these, however, only 1 SNP showed nominal significant association in the other patient group. Based on this evidence, we performed a pathway-based analysis to understand the biological mechanisms underlying this difference. Pathway analysis showed 52 biological processes associated with joint damage in ACPA-negative RA and 32 pathways in the ACPA-positive group, with only two shared biological processes between the two groups. Fc Gamma receptor mediated phagocytosis was the topmost biological process associated with erosions specifically in ACPA-negative RA and Signalling by Fibroblast Growth Factor mutants was the top process specific for ACPA-positive patients. Conclusion: The results from our study provide suggestive evidence that the genetic basis for joint damage is different according to the presence of ACPA. Replication of the new candidate loci in an independent patient cohort is underway. References: [1]Lopez-Lasanta, M., Julià, A., Maymó, J., Fernández-Gutierrez, B., Ureña-Garnica, I., Blanco, F. J., ... & Tornero, J. (2015). Variation at interleukin-6 receptor gene is associated to joint damage in rheumatoid arthritis. Arthritis research & therapy, 17 (1), 242. Disclosure of Interests: Antonio Julià: None declared, Francisco Blanco: None declared, Benjamin Fernandez: None declared, Antonio Gonzalez: None declared, Juan D: None declared, Joan Maymó: None declared, Mercedes Alperi-López: None declared, Alejandro Olive: None declared, Héctor Corominas Speakers bureau: Abbvie, Lilly, Pfizer, Roche, Victor Martinez Taboada: None declared, Isidoro González-Álvaro Grant/research support from: Roche Laboratories, Consultant of: Lilly, Sanofi, Paid instructor for: Lilly, Speakers bureau: Abbvie, MSD, Roche, Lilly, Antonio Fernandez-Nebro: None declared, Alba Erra: None declared, Simon Sánchez Fernandez: None declared, Núria Palau: None declared, Maria Lopez Lasanta: None declared, Adrià Aterido: None declared, Jesús Tornero: None declared, Sara Marsal: None declared